The effect of macromolecular crowding on chaperonin-mediated protein folding - Martin, Jörg (The National Academy of Sciences of the USA, 1997)
The cylindrical chaperonin GroEL and its cofactor GroES mediate ATP-dependent protein folding in Escherichia coli. Recent studies in vitro demonstrated that GroES binding to GroEL causes the displacement of unfolded polypeptide into the central volume of the GroEL cavity for folding in a sequestrated environment. Resulting native protein leaves GroEL upon GroES release, whereas incompletely folded polypeptide can be recaptured for structural rearrangement followed by another folding trial. Additionally, each cycle of GroES binding and dissociation is associated with the release of nonnative polypeptide into the bulk solution. Here we show that this loss of substrate from GroEL is prevented when the folding reaction is carried out in the presence of macromolecular crowding agents, such as Ficoll and dextran, or in a dense cytosolic solution. Thus, the release of nonnative polypeptide is not an essential feature of the productive chaperonin mechanism. Our results argue that conditions of excluded volume, thought to prevail in the bacterial cytosol, increase the capacity of the chaperonin to retain nonnative polypeptide throughout successive reaction cycles. We propose that the leakiness of the chaperonin system under physiological conditions is adjusted such that E. coli proteins are likely to complete folding without partitioning between different GroEL complexes. Polypeptides that are unable to fold on GroEL eventually will be transferred to other chaperones or the degradation machinery.